2010
DOI: 10.1089/jmf.2010.1191
|View full text |Cite
|
Sign up to set email alerts
|

Ginger Extract Inhibits Human Telomerase Reverse Transcriptase and c-Myc Expression in A549 Lung Cancer Cells

Abstract: The rhizome of ginger (Zingiber officinale Roscoe) has been reputed to have many curative properties in traditional medicine, and recent publications have also shown that many agents in ginger possess anticancer properties. Here we show that the ethyl acetate fraction of ginger extract can inhibit the expression of the two prominent molecular targets of cancer, the human telomerase reverse transcriptase (hTERT) and c-Myc, in A549 lung cancer cells in a time- and concentration-dependent manner. The treated cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
4
20
0
Order By: Relevance
“…Our strongest indication of a treatment effect on proliferation was the estimated effect on hTERT expression. A decrease in hTERT expression is consistent with previous reports, which found that ginger inhibited hTERT and c-Myc expression in human non-small lung cancer cells (24). While the estimated treatment effect on our other marker of proliferation MIB-1 was not as strong, the estimated effect was more pronounced in the upper sections of the colorectal crypts, suggesting that ginger may decrease proliferation in the parts of the colorectal crypts most exposed to bowel lumen carcinogens.…”
Section: Discussionsupporting
confidence: 93%
“…Our strongest indication of a treatment effect on proliferation was the estimated effect on hTERT expression. A decrease in hTERT expression is consistent with previous reports, which found that ginger inhibited hTERT and c-Myc expression in human non-small lung cancer cells (24). While the estimated treatment effect on our other marker of proliferation MIB-1 was not as strong, the estimated effect was more pronounced in the upper sections of the colorectal crypts, suggesting that ginger may decrease proliferation in the parts of the colorectal crypts most exposed to bowel lumen carcinogens.…”
Section: Discussionsupporting
confidence: 93%
“…The hTERT promoter contains binding sites for c-Myc, and there evidence that c-Myc may increase hTERT expression [7375]. Recently, it has been demonstrated that the ethyl acetate fraction of ginger extract inhibited growth of A549 lung carcinoma cells through downregulation of hTERT and c-Myc expression [76]. The findings in this study directly recapitulate these earlier studies, since treatment of MCF-7 and MDA MB-231 cells with ginger extract resulted in a significant reduction in the protein level of Bcl-2, which coincided with a parallel reduction in the protein levels of c-Myc and hTERT.…”
Section: Discussionmentioning
confidence: 99%
“…8 Many plant extracts have been reported to inhibit cell proliferation through the down regulation of c-myc expression. 9,10 In this study, the c-myc expression was suppressed by γ-sitosterol which was isolated from S. crispus. To observe the effectiveness of γ-sitosterol in suppressing oncogenes, mRNAs was extracted from the treated cells.…”
Section: Discussionmentioning
confidence: 84%